Anti-M Alloimmunization: Management and Outcome at a Single Institution - Bethany Stetson; Scott Scrape; Kara Beth Markham (Thieme Medical Publishers, Inc., 2017)
Abstract Objective The objective of this study was to review the management strategies and outcomes in gravidas with anti-M alloimmunization over 15 years. Study Design Data collected from 195 pregnant patients with anti-M antibodies from July 2000 through June 2016 were reviewed retrospectively. We analyzed indirect antiglobulin test titer results, paternal or fetal/neonatal M antigen status, antepartum course, and perinatal outcomes. Results Anti-M antibodies were found in 146 women and 195pregnancies. Among those with positive indirect antiglobulin tests, 193 pregnancies had titers at or below 1:4. Only one patient with an initial low titer experienced a more than twofold increase to a titer 1:64. Two women underwent an amniocentesis and cordocentesis. Ninety-five (73.6%) of the 129 infants tested were positive for the M antigen. Nine infants required phototherapy. There were no cases of hemolytic disease of the fetus or newborn, mild or severe. Conclusion The incidence of severe hemolytic disease of the newborn due to anti-M is extremely low. We found no cases in our review of 195 pregnancies, despite several cases of severe hemolytic disease of the newborn reported in the literature. We have created an algorithm for the management of anti-M antibodies in pregnancy based on our data and extensive literature review.